The Implementation of the KMI Curriculum in Shaping Tahfidz Students' Habitus: Insights from a Qualitative Study - Ayatullah Khumaini Barnabas; Suripto (Al-Qalam Institue, 2026)
This study aims to examine how the Kulliyatul Mu'allimin Al-Islamiyah (KMI) curriculum shapes the habitus of Tahfidz students within an integrated Islamic boarding school education system. A qualitative case study approach was employed to explore the curriculum implementation in its natural context. Data were collected through participatory observation, in-depth interviews with school leaders, curriculum coordinators, teachers, and students, as well as document analysis. The data were analyzed using Miles and Huberman’s interactive model and interpreted through Pierre Bourdieu’s theory of habitus, field, and capital. The findings indicate that the KMI curriculum fosters students’ habitus through three interconnected mechanisms: the development of discipline through structured daily routines and worship practices, the cultivation of academic-Tahfidz competence through the integration of Qur’anic memorization and multilingual learning, and the strengthening of independence and leadership through student organizational activities. Furthermore, the curriculum facilitates the transformation of spiritual capital into symbolic and social capital, reinforcing sustainable character formation. These findings imply that an integrated curriculum grounded in continuous habituation can serve as an effective model for cultivating students’ religious character, leadership capacity, and holistic educational development in Islamic boarding school settings.